The Effect of Self-Efficacy and Math Anxiety on Students' Non-Routine Mathematics Problem Solving Ability - Muharani, Dwi Rizki; Sucipto, Lalu (IJECA (International Journal of Education and Curriculum Application), 2023)
The lack of research on the impact of self-efficacy and mathematics anxiety on non-routine mathematics problem solving ability emphasizes the importance of this study. While previous studies have focused on psychological factors in the context of learning mathematics, limited attention has been paid to how these factors influence students' ability to solve non-routine mathematical problems. This study aims to fill this gap by identifying the role of self-efficacy and math anxiety in students' ability to cope with and solve non-routine math problems. The main objective of this study is to measure the impact of self-efficacy and math anxiety on students' ability to solve non-routine math problems. By exploring these psychological factors, this study aims to make a significant contribution to our understanding of the factors that influence student performance in the context of solving complex non-routine mathematical problems.